English Speaking Difficulties Encountered by Tourism Department Students’ in EFL Public Interactions: A qualitative study - Ismail Koerniawan Mohammad; Hasanuddin Fatsah; Abid Abid (Univeristas Negeri Gorontalo, 2022)
Mastering English facilitates students’ preparation for professional job applications. In the context of tourism school, learning the language, therefore, is a must. The study reported in this article explores the difficulties in speaking English encountered by a group of Indonesian learners of English and how they anticipated their perceived difficulties. A qualitative research approach was employed for data collection and analysis. Participants were from a Tourism Department of a university in the Province of Gorontalo, Indonesia, who voluntarily agreed to join in the interview sessions. Findings showed that most participants struggled to communicate in English, particularly when interacting with foreigners. The difficulties include a lack of vocabulary and comprehension of certain accents. In addition, it was found that in anticipating those difficulties, students employed regular English use practices, gestures, and information technology assistance. The study suggests that frequent meaningful English practices in and outside the English classroom should be facilitated, and the use of relevant technological tools for fostering English language practices be promoted.